Application of the Sosiodrama Learning Model to Improve Javanese Language Learning Achievement in Class VIII G Students of Junior High School 2 Sewon Academic Year 2022/2023 - Hestini Nugraningrum Utami (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This study aims to find out whether the Sosiodrama learning model can improve Javanese learning achievement in class VIII G students of SMP Negeri 2 Sewon for the 2022/2023 academic year. This research is a classroom action research consisting of two cycles. Each cycle follows the stages of the Kemmis and Taggart models which include four components, namely planning, action, observation, and reflection. The data collected in this study is the result of activities related to the implementation of learning with the sociodrama model. Data collection techniques using test and non-test techniques with quantitative and qualitative descriptive approaches. The results showed that the use of the Sosiodrama model in Javanese language learning activities could improve student achievement and learning activities in the learning process.